Multicenter experience of adult medulloblastoma: A study of Anatolian Society of Medical Oncology (ASMO) - (:unkn) unknown (ZERBINIS MEDICAL PUBL, 2016)
Purpose: Medulloblastoma (MB) is rarely seen in adults. For adjuvant therapy in adults the same therapy protocols used in pediatric cases are used. The present study retrospectively evaluated the data of MB patients who were treated in different Oncology Centers in Turkey. Methods: The data of 60 adult patients with MB from 8 Oncology Centers diagnosed between 2005 and 2012 were retrospectively analyzed. Results: The median patient age was 28.8 years (range 16-54). The administered chemotherapy included procarbazine-Flomustin vincristine (group A, N=31) and cyclophosphamide/ifosfamide+vincristine+cisplatin (group B, N=13). Median chemotherapy courses were 4 (range 1-8). Median progression free survival (PFS) was 76 months and median overall survival (OS) has not been reached in both groups. In young female patients and in those who received adjuvant chemotherapy, median PFS and OS were longer but without statistical significance. Mean PFS and OS were 65.9 months and 101.2 months in group A and 113.6 months and 141.6 months in group B, respectively. Conclusion: Improved survival results were obtained in women, in patients aged below 25 years, in those who underwent gross total excision (GTE) and in those who received adjuvant therapy with cyclophosphamide/ifosphamide.
Keywords: adjuvant; adult; chemotherapy; medulloblastoma; PROGNOSTIC-FACTORS; BRAIN-TUMORS; CHEMOTHERAPY; RADIATION; RADIOTHERAPY; CHILDHOOD; SURVIVAL; CHILDREN; THERAPY